Navigating Loneliness: Exploring the Impact of Self-Esteem, Social Support, and Personality Traits on Transient University Students - Putri, Resti Adinia; Syukrilla, Wara Alfa; Nihayah, Zahrotun (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2024)
Abstract: Transient university students who experience loneliness might be exposed to decreased mental well-being threats, such as decreased happiness, depression symptoms, stress, and anxiety. Therefore, this study aims to examine whether there is an effect of self-esteem, social support, personality, and demographic factors on the loneliness of students who study outside their hometown city. This study was conducted cross-sectionally with multiple linear regression analysis and the sample was selected using snowball sampling technique. The sample of this study amounted to 225 transient university students in Jabodetabek. The instruments used are The Revised UCLA Loneliness Scale, The State Self-Esteem Scale, the Multidimensional Scale of Perceived Social Support, and the Extrovert and Introvert Personality Inventory. The results showed that self-esteem had the largest significant effect (β=-0.583,p